C++ and object-oriented programming (Prentice Hall, 1997)
"An accessible introduction to the C++ language and object-oriented design for students and programmers who know at least one modern high-level language. Understanding that the greatest challenge in learning C++ is being able to think in terms of classes and objects, Kip Irvine introduces these topics immediately as concepts in the context of real-world applications such as e-mail systems and automated bank tellers." "Through extensive use of short program examples and case studies, the author provides a concise, clear discussion of C++ syntax. He includes extensive coverage of the object model concept and how to use an object-oriented approach to design. Throughout the book, the importance of careful analysis and design of programs is evidenced."